Mathematics Literacy Based on The Self-Regulated Learning on Problem-Based Learning Assisted with Electronic Module - Ningtyas, Nurul Ainna; Rochmad, Rochmad; Hidayah, Isti (Unnes Journal of Mathematics Education Research, 2022)
Mathematics literacy and self-regulated learning have important roles for individuals to make decisions and solve problems in life. This research describes the learners' mathematics literacy of the learners based on self-regulated learning by implementing problem-based learning assisted with an electronic module. The research subjects consisted of the 20 tenth graders of TOKR 1, in the academic year of 2022/2023. The researchers collected the data with a test method, questionnaire, observation, documentation, and interview. The results showed the mathematics literacy test achievement, TL M of the learners, based on the learning self-directedness with problem-based learning and the assistance of various electronic modules. The mathematics literacy based on the learning self-directedness showed that the learners had high TLM and learning self-directedness to understand and master six indicators; the learners with moderate TLM and learning self-directedness could master four indicators; and the learners with low TLM and self-directedness could only master two indicators.